2015
DOI: 10.3389/fmicb.2015.00225
|View full text |Cite
|
Sign up to set email alerts
|

Microbial abundance in surface ice on the Greenland Ice Sheet

Abstract: Measuring microbial abundance in glacier ice and identifying its controls is essential for a better understanding and quantification of biogeochemical processes in glacial ecosystems. However, cell enumeration of glacier ice samples is challenging due to typically low cell numbers and the presence of interfering mineral particles. We quantified for the first time the abundance of microbial cells in surface ice from geographically distinct sites on the Greenland Ice Sheet (GrIS), using three enumeration methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 72 publications
9
85
0
Order By: Relevance
“…4.6). Cells can be counted in field samples using traditional microscopy or flow cytometry, although the two methods may produce different results (Stibal et al, 2015). The chlorophyll content of a sample has traditionally been used as a proxy for biomass; however, the amount of chlorophyll in an individual cell is species-specific and changes over time as a mechanism of photoacclimation (e.g.…”
Section: Measuring Biomassmentioning
confidence: 99%
“…4.6). Cells can be counted in field samples using traditional microscopy or flow cytometry, although the two methods may produce different results (Stibal et al, 2015). The chlorophyll content of a sample has traditionally been used as a proxy for biomass; however, the amount of chlorophyll in an individual cell is species-specific and changes over time as a mechanism of photoacclimation (e.g.…”
Section: Measuring Biomassmentioning
confidence: 99%
“…The observations show however, that the albedo continues to decline throughout the melt season to around 0.2 on the 30 June and even lower by the end of the summer. These low values reflect the formation of cryoconite and the accumulation of dirt and impurities that melt out of the ice as well as microbial activity on the glacier surface (Stibal et al, 2015) but QAS_L lies in the lowest part of the ablation zone and has much lower albedo values than typical for most of the ablation zone in Greenland, (Ryan et al, 2017), as also shown in Fig. 10.…”
Section: Modified Surface Scheme Resultsmentioning
confidence: 82%
“…Spatial variability in carbon and nutrient concentrations and microbial abundance and activity has been reported from the GrIS (e.g., Hodson et al, 2010;Stibal et al, 2010Stibal et al, , 2012bStibal et al, , 2015aTelling et al, 2012;Yallop et al, 2012). However, direct measurements exist from very few discreet locations, and upscaling from point measurements to the whole ice sheet may introduce large errors.…”
Section: Modeling the Supraglacial Ecosystemmentioning
confidence: 99%
“…Microbial cells deposited with snow may remain on the ice surface after the snow has melted and become part of the surface ice community, or they can be flushed from the ice sheet surface with meltwater (Cameron et al, 2015). Bare ice is exposed seasonally around the margins of the ice sheet and hosts a high abundance of algae (Uetake et al, 2010;Yallop et al, 2012) and other microorganisms (Stibal et al, 2015a;Cameron et al, 2016). The algae are important primary producers in the ecosystem and may contribute to surface melting via darkening the ice due to pigment production Yallop et al, 2012).…”
Section: The Supraglacial Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation